A Measurement Approach to the Bourdieusian Social Capital within Facebook Institutional Pages - Cunha, Kaique Matheus Rodrigues; da Costa, Renata Luiza; Gomes, Alan Keller (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2021)
We present in this paper a measurement approach to the Bourdieusian Social Capital (BSC) within Facebook Institutional Pages (fanpages). Supported by Pierre Bourdieus Theory, we researched for guidelines to identify and capture data related to sociability practices, for instance actions such as Post, Like, Comment and Share. We use such data to extract generalized sequential patterns (ordered lists) by modelling social interactions as sequences of actions. Next, we also use such data to measure the frequency of occurrence and count the number of actions performed which it is part of each sequence. These values are used to measure the effective mobilization capacity of each page. Finally, the volume of BSC accumulated within a page is measured by balancing the effective mobilization capacity, the number of social interactions and the number of followers. The results obtained are aligned to the Bourdieus Theory and our measurements allow to compute the continuous sociability effort of each fanpage to maintain and expand its BSC.